More answers

x2 + (x-2)2 = (x-4)2

Eliminate parentheses:

x2 + x2 - 4x + 4 = x2 - 8x + 16

Collect terms on the left side:

2x2 - 4x + 4 = x2 - 8x + 16

Subtract x2 from each side:

x2 - 4x + 4 = -8x + 16

Add 8x to each side:

x2 + 4x + 4 = 16

Subtract 16 from each side:

x2 + 4x - 12 = 0

Factor the left side:

(x - 2) (x + 6) = 0

from which:

x = 2

x = -6

Q: What is x squared plus x-2 squared equals x-4 squared?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

For any x ≠ 0, x2 -10/x2 - 4 +3x/x2 - 4 LCD = x2, multiply each term by their missing element of LCD = (x4 + 10 +3x - 8x2)/x = (x4 - 8x2 + 3x + 10)/x2

x4 +x2 =x2 (x2+1)

Since it's x2*x2, you would add the exponents giving you x4

-6x3 + 4x7 - 0.8x2 + x4 - 5x5 = 4x7 - 5x5 + x4 - 6x3 - 0.8x2 = x2 (4x5 - 5x3 + x2 - 6x - 0.8)

(xn+2-1)/(x2-1)ExplanationLet Y=1+x2+x4+...+xn. Now notice that:Y=1+x2+x4+...+xn=x2(1+x2+x4+...+xn-2)+1Y+xn+2=x2(1+x2+x4+...+xn-2+xn)+1Y+xn+2=x2*Y+1Y+xn+2-x2*Y=1Y-x2*Y=1-xn+2Y(1-x2)=1-xn+2Y=(1-xn+2)/(1-x2)=(xn+2-1)/(x2-1)

Related questions

No.

For any x ≠ 0, x2 -10/x2 - 4 +3x/x2 - 4 LCD = x2, multiply each term by their missing element of LCD = (x4 + 10 +3x - 8x2)/x = (x4 - 8x2 + 3x + 10)/x2

4X + 2x = 1. Where x = 0.166666666666666666666666666666666666666 recurring.

(X2) (X2) = X4 x squared multiplied by x squared is x raised to the 4th power.

if c = x2 then cx2 = x4

x(x4+x3+x2+x+1)

x4 +x2 =x2 (x2+1)

Since it's x2*x2, you would add the exponents giving you x4

(x + y)2 = x2 + 2xy + y2 So x2 + y2 = (x + y)2 - 2xy = a2 - 2b Then (x2 + y2)2 = x4 + 2x2y2 + y4 So x4 + y4 = (x2 + y2)2 - 2x2y2 = (a2 - 2b)2 - 2b2 = a4 - 4a2b + 4b2 - 2b2 = a4 - 4a2b + 2b2

x2*x2...You would add the two exponents like this x(2+2), making it x4.

-6x3 + 4x7 - 0.8x2 + x4 - 5x5 = 4x7 - 5x5 + x4 - 6x3 - 0.8x2 = x2 (4x5 - 5x3 + x2 - 6x - 0.8)

(xn+2-1)/(x2-1)ExplanationLet Y=1+x2+x4+...+xn. Now notice that:Y=1+x2+x4+...+xn=x2(1+x2+x4+...+xn-2)+1Y+xn+2=x2(1+x2+x4+...+xn-2+xn)+1Y+xn+2=x2*Y+1Y+xn+2-x2*Y=1Y-x2*Y=1-xn+2Y(1-x2)=1-xn+2Y=(1-xn+2)/(1-x2)=(xn+2-1)/(x2-1)